Enrichment and chemical fractionation of plant nutrients, potentially toxic and economically valuable elements in digestate from mesophilic and thermophilic fermentation. (June 2023) - Zaffar, Nazia; Ferchau, Erik; Heilmeier, Hermann; Boldt, Christin; Prada Salcedo, Luis Daniel; Reitz, Thomas; Wiche, Oliver
Abstract: This study investigated the effect of mesophilic (37 °C) and thermophilic (55 °C) digestion on the enrichment and fractionation of plant nutrients (P, Mn, Fe), potentially toxic elements (Cd, Cr, Pb, As, Cu, Ni, Co, Zn) and economically valuable elements (Ge, rare earth elements REE). Batch experiment was conducted with the substrates of Phalaris arundinacea and inoculum for 40 days and the latter digestate was collected for further analysis. Digestate from selected reactors was filtered through 0.2 μm syringe filters to separate dissolved elements from the particulate. The solid digestate was extracted with ammonium acetate (pH 7 and pH 5) to determine the extraction of mobile/exchangeable and acid soluble elements, respectively. In fresh digestate, element concentration increased by more than 20–100% especially Ge (94%) and REEs (119%) and pH (6.5–7.9) was significantly higher compared to mesophilic (6.1–7.5). In dried digestate, thermophilic digestion showed increased enrichment of Fe, Co, Cu, Zn, Cr, As, Cd, Pb and especially Ge (193%) and REEs (90%) compared to mesophilic indicating a strong enrichment in thermophilic digestion. Considering both operating conditions 5% of elements were present in the liquid, less than 30% were exchangeable and acid soluble and more than 70% were stabile bound into solids. Thermophilic conditions significantly increased the portion of dissolved and labile-bound elements in the digestate. Reactor temperature offers a promising way to use digestate as a secondary raw material for element recovery in the spirit of phytomining, which contributes to a "cascade use" of digestate in the circular economy. Highlights: Anaerobic fermentation concentrates Ge, REE and other trace elements in digestate. Element enrichment is significantly enhanced under thermophilic conditions. Thermophilic condition increased the labile elements in digestate. Optimization of reactor temperature is promising for element recovery.